2007
DOI: 10.1002/hep.21966
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnosis of hepatic nodules 20 mm or smaller in cirrhosis: Prospective validation of the noninvasive diagnostic criteria for hepatocellular carcinoma

Abstract: This study prospectively evaluates the accuracy of contrast-enhanced ultrasound (CEUS) and dynamic magnetic resonance imaging (MRI) for the diagnosis of nodules 20 mm or smaller detected during ultrasound (US) surveillance. We included 89 patients with cirrhosis [median age, 65 years; male 53, hepatitis C virus 68, Child-Pugh A 80] without prior hepatocellular carcinoma (HCC) in whom US detected a small solitary nodule (mean diameter, 14 mm). Hepatic MRI, CEUS, and fine-needle biopsy (gold standard) (FNB) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

30
693
5
44

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 927 publications
(772 citation statements)
references
References 30 publications
30
693
5
44
Order By: Relevance
“…Therefore, this is only a level 4 study. Forner et al 56 also validated the old AASLD guidelines in their study. According to these guidelines, 2 concordant imaging methods are required for the diagnosis of HCC.…”
Section: Question 4 Are There Studies Validating the Current Guidelimentioning
confidence: 82%
See 4 more Smart Citations
“…Therefore, this is only a level 4 study. Forner et al 56 also validated the old AASLD guidelines in their study. According to these guidelines, 2 concordant imaging methods are required for the diagnosis of HCC.…”
Section: Question 4 Are There Studies Validating the Current Guidelimentioning
confidence: 82%
“…In the more recent literature, 2 additional level 1b studies could be identified 56,57 (Tables 6 and 7). In the study by Forner et al, 56 only patients with newly detected lesions between 5 and 20 mm in size were included, and CEUS and MRI were used as imaging modalities.…”
Section: Level 1b Studiesmentioning
confidence: 99%
See 3 more Smart Citations